Nitrogen cycling in an Antarctic ecosystem 2. Estimation of the amount of nitrogen fixation in a moss community on East Ongul Island - Nakatsubo, Takayuki; Ino, Yoshio (Ecological Research, 1987)
Abstract Nitrogen fixation by cyanobacteria in a moss community on East Ongul Island (69°00'S 39°35′E), Antarctica was investigated using the acetylene reduction method. The mean acetylene reduction rate at 10°C and 200 μE·m −2 ·s −1 photosynthetically active radiation was 7.12 nmol C 2 H 4 per square centimeter of moss community per hour. The effects of temperature, radiation, desiccation and rehydration on the acetylene reduction rates were examined. A simple predictive model was constructed in order to estimate the amount of nitrogen fixed in the field. Using this model, the daily amount of nitrogen fixation was calculated from microclimatic data (temperature and radiation) measured in the experimental field at Syowa Station on East Ongul Island between 1983 and 1984. The cumulative amount of nitrogen fixation in the growing season during this period was estimated to be 329 mg N per square meter of moss community. It is suggested that nitrogen fixation by cyanobacteria in the moss community is important as a nitrogen source for the community growth on East Ongul Island.